2018
DOI: 10.1111/jasp.12552
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of scary numbers: The effect of perceived trends on future estimates, severity ratings, and help‐allocations in a cancer context

Abstract: Statistical information such as death risk estimates is frequently used for illustrating the magnitude of a problem. Such mortality statistics are however easier to evaluate if presented next to an earlier estimate, as the two data points together will illustrate an upward or downward change. How are people influenced by such changes? In seven experiments, participants read mortality statistics (e.g., number of yearly deaths or expert‐estimated death risks) made at two points of time about various cancer types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 47 publications
1
21
3
Order By: Relevance
“…One recent study demonstrated that when people receive revised probability estimates from two experts, they find these two experts to agree more if they have revised their estimate in the same rather than in opposite directions (Hohle & Teigen, ). This adds to previous findings of a trend effect in revisions of probability estimates (Erlandsson, Hohle, Løhre, & Västfjell, ; Hohle & Teigen, ; Maglio & Polman, ), where people expect that revisions will continue in the same direction (e.g., a probability that has increased from 60% to 70% will become even higher in the future).…”
Section: Discussionsupporting
confidence: 74%
“…One recent study demonstrated that when people receive revised probability estimates from two experts, they find these two experts to agree more if they have revised their estimate in the same rather than in opposite directions (Hohle & Teigen, ). This adds to previous findings of a trend effect in revisions of probability estimates (Erlandsson, Hohle, Løhre, & Västfjell, ; Hohle & Teigen, ; Maglio & Polman, ), where people expect that revisions will continue in the same direction (e.g., a probability that has increased from 60% to 70% will become even higher in the future).…”
Section: Discussionsupporting
confidence: 74%
“…Everyday observations and research show that people do not need much evidence to infer a trend. Two data points may be sufficient to indicate a process of growth or decline and can lead observers to formulate hypotheses of monotonous and even linear increases or decreases (Erlandsson, Hohle, Løhre, & Västfjäll, ; Hohle & Teigen, ). When probabilities are changed or revised, it is easy to imagine that a process of continued revision will take place.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has replicated the trend effect for interval forecasts. A forecast where the interval for expected outcomes had widened was predicted to continue widening, while a narrowed interval was believed to become still narrower in the future (Løhre, 2017). Even single forecasts can suggest a trend, depending upon the way they are described.…”
Section: The Trend Effectmentioning
confidence: 99%
“…Trends created by revised probabilities may affect actual behavior. People were willing to donate more money to research on a cancer type whose death risk has increased rather than decreased (Erlandsson, Hohle, Løhre, & Västfjäll, 2017), and preferred a product whose risk of a defect was adjusted downwards compared to upwards (Maglio & Polman, 2016). Importantly, in all these studies the current forecasts were the same, only the previous forecasts differed by being higher or lower than the most recent one.…”
Section: The Trend Effectmentioning
confidence: 99%
See 1 more Smart Citation